Arbetslivsetnologi Professioner i nyliberala organisationer: Inledning - Nilsson, Gabriella; Sjöstedt Landén, Angelika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
During the entire 20th century, interest in work and work life as a cultural phenomenon was central to the development of Ethnology as an academic discipline: from an interest in the work and tools of peasant communities, to extensive research on different occupational cultures, including working class ones, to a focus on the processes of professionalization and on policy changes that have an impact on working life. However, with labor market changes in neo-liberal society, such as increasing requirements of flexibility, measurability, efficiency, and implementation of evidence-based practices, ethnological interest in work seems to have waned. In this special issue, we wish to stress the importance of this field of study to Ethnology, and urge the resumption of research in it, which would include posing vital questions about how changes in working life are articulated, implemented and experienced. There is a need for new analytical "takes" on how work life and everyday life intertwine in neo-liberal society. How are work situations influenced by the interjection of new discursive ideals and logics? How are the identities and subjectivities of employees affected? How are new power structures formed and old ones reproduced? With a variety of contributions in this issue that draw on a range of organizational and professional contexts, we aim to highlight the impact these changes in working life have had in the everyday lives of people both inside and outside such settings.